Pain during the first year after scoliosis surgery in adolescents, an exploratory, prospective cohort study - de Leeuw, Thomas G.; Boerlage, Anneke A.; van West, Hanneke M.; Renkens, Jeroen J. M.; van Rosmalen, Joost; Staals, Lonneke M. E.; Weber, Frank; Tibboel, Dick; de Wildt, Saskia N. (Frontiers in Pediatrics, 2024)
Objective Approximately 50% of adolescents who have undergone scoliosis surgery still experience severe pain one year postoperatively. We explored the postoperative pain trajectory and the potential value of preoperative Thermal Quantitative Sensory Testing (T-QST) as predictor of chronic postsurgical pain after scoliosis surgery. Design Single-center prospective cohort study in adolescents undergoing scoliosis surgery. Outcomes Prevalence of chronic postsurgical pain (CPSP) one year after scoliosis surgery and postsurgical pain course during this year. The need for rescue medication and the relationship between pre-operative T-QST, acute pain and CPSP. Results Thirty-nine patients (mean age 13.9 years; SD 1.9 years) completed the study. One year postoperatively, ten patients (26%) self-reported pain [numeric rating scale (NRS) score ≥ 4]) when moving and two (5%) when in rest. Four of these patients (10.3%) experienced neuropathic pain. The pre-operative cold pain threshold was lower (p = 0.002) in patients with CPSP at 12 months. Preoperative cold and heat pain thresholds were correlated with the number of moderate or severe pain reports (NRS ≥ 4) in the first week postoperatively (r -.426; p = 0.009 and r.392; p = 0.016, respectively). Conclusions One year after scoliosis surgery, a significant part of patients (26%) still reported pain, some with neuropathic characteristics. Better diagnosis and treatment is needed; our study suggests that T-QST could be further explored to better understand and treat children with this negative outcome.